Pancreatic Exocrine Enzymes and Intrapancreatic Protein Synthesis in Acute Oedematous Pancreatitis. Issue 1 (1994) - Kinami, Yoshio; Kita, Ichiro; Kojima, Yasuhiko; Takashima, Shigeki
Abstract : Changes in serum and intrapancreatic enzyme content and protein synthesis in pancreas were studied in acute oedematous pancreatitis (AOP). Male Wistar rats ( n = 111) were divided into 2 groups, controls with a sham operation and those with AOP. Serum amylase levels rose immediately after the procedure causing AOP and then fell gradually, while serum lipase and ribonuclease levels remained higher than control values over 48h. ( p < 0.05, 0.01). Serum deoxyribonuclease (DNase) II levels were unchanged. Intrapancreatic enzyme levels were scarcely affected by AOP. 3 H-leucine uptake into pancreatic tissue of rats with AOP was decreased throughout the study ( p < 0.001), but some protein synthesis continued. Intrapancreatic enzyme contents are maintained despite diffusion into the blood because the pancreas retain its ability to synthesize enzymes.